IMPLEMENTASI METODE COOPERATIVE TIPE MAKE A MATCH DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN HASIL BELAJARSISWA KELAS IX DI SMPN 1 AMPEK ANGKEK - Renata Juliana Putri; Deswalantri (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Schools often experience problems in the process because the methods used are too monotonous and the methods used are not many, causing low learning outcomes. These problems indicate that students are less active when learning. The purpose of this study was to find out how much the contribution of the introduction of the Make A Match Type Cooperative method to improving students' Islamic learning outcomes. This type of research is a pre- experimental, one-group pre-post-test design. The research involved all 209 students of class IX which were divided into 7 classes. Although the sample is 32 people from class IX 1. The sampling technique is purposive sampling. This research tool uses test questions. The collected data was processed using descriptive statistical analysis and inferential statistical analysis. Based on the results of statistical analysis which describes 62.77. Based on the results of descriptive statistical analysis of PAI learning outcomes after using the Cooperative Type Make A Match method, it can be seen that the average is 85.35. Based on the results of the Independent Sample t Test. The hypothesis test was carried out on student learning outcomes data. It is known that the value of statistical calculations carried out to prove the hypothesis is Tcount -8.486 and Ttable -2.042. Test criteria: If Tcount is less than Ttable then H_0 is rejected. Because Tcount is smaller than Ttable, then H_1 is accepted. Thus it can be concluded that the Cooperative Type Make A Match method has a significant effect on improving student Islamic education learning outcomes.